Supramolecular architectures sustained by arene-C-H⋯π(quasi-chelate ring) interactions in the crystal structures of copper(I) complexes - Zukerman-Schpector, J.; Yeo, C.I.; Tiekink, E.R.T. (De Gruyter, 2016)
A review of the crystallographic literature is presented whereby structures featuring a quasi-six-membered chelate ring of the type CuCl⋯HNCS were evaluated for the presence of intermolecular C-H⋯π(quasi-chelate) interactions. These are shown to stabilise crystal structures leading to zero-, one-, two- and even three-dimensional architectures. Details of these interactions are described and a comparison to analogous interactions formed intramolecularly has been made. The C-H⋯π(quasi-chelate) interactions in these structures occur in one-third of structures where such contacts can potentially form.